Improving Tuberculosis Patient Adherence through Collaborative Governance and Public Values in Palembang City - Fenty Aprina; Al Fitri; Muhammad Husni Thamrin; Sriati Sriati (Eduvest - Journal of Universal Studies, 2025)
Tuberculosis (TB) remains one of the most significant public health issues globally, with high morbidity and mortality rates. The City of Palembang, Indonesia, has been identified as a high-burden area for TB, which poses challenges in achieving the national and global elimination targets by 2030. This study explores the roles of collaborative governance and public value in enhancing patient adherence to TB treatment in Palembang. Using qualitative research methods, including in-depth interviews and focus group discussions (FGD) with TB patients, healthcare providers, and stakeholders, this research aims to understand how collaborative governance structures and patients' perceptions of public value influence treatment adherence. The study finds that effective collaboration between government agencies, healthcare facilities, and non-governmental organizations (NGOs) plays a critical role in improving TB service delivery and treatment adherence. However, challenges remain in the areas of data sharing, coordination, and resource allocation, which hinder the full potential of collaborative governance. Furthermore, the research reveals that patients' adherence to treatment is significantly influenced by their perception of public value, such as feeling respected, having access to equitable healthcare, and trusting the healthcare system. Patients who feel valued and treated with dignity are more likely to adhere to their treatment regimen, while stigma and discrimination remain significant barriers to adherence.